Eucalyptus spp. WOOD PRICE FORECASTING MODEL - Soares, Naisy Silva (2015)
The objective of this paper was to establish a price forecasting model of Eucalyptus spp. wood in Itapeva (SP) and Bauru (SP), using Box & Jenkins (1976) methodology in monthly observations, from May 2002 to January 2008. The results shows that the appropriate models for forecasting Eucalyptus spp. wood price in Itapeva (SP) and Bauru (SP) were, respectively, ARIMA (0,1,4) and ARIMA (2,1,2).